Northerners and Southerners Differ in Conflict Culture. (23rd September 2018) - Van de Vliert, Evert; Conway, Lucian Gideon
Abstract: The present study uses regression analysis of existing cross‐national data sets to demonstrate that ingroup–outgroup discrimination and intergroup conflict management vary more along the north–south (latitudinal) axis than along the east–west axis of the Earth. Ingroup favoritism, outgroup rejection, political oppression, legal discrimination, and communication bullying are all less prevalent among Northerners than among Southerners in the Northern Hemisphere, but more prevalent among Northerners than among Southerners in the Southern Hemisphere. These findings provide a rich source for further research into how social conflicts are habitually experienced and handled by residents of northern versus southern habitats. A supplementary analysis specifies the extent to which ecological stressors—thermal stress, hydraulic stress, pathogenic stress, and subsistence stress—help explain why there are oppositely sloping north–south gradients of conflict culture above and below the equator. Taken in total, these results demonstrate the importance of considering latitude in forming a deeper understanding of conflict management and negotiation.